Development of UV Spectrophotometric Procedures for Determination of Amlodipine and Celecoxib in Formulation: Use of Scaling Factor to Improve the Sensitivity - Attimarad, Mahesh; Venugopala, Katharigatta Narayanaswamy; Aldhubiab, Bandar E.; Nair, Anroop Balachandran; SreeHarsha, Nagaraja; Pottathil, Shinu; Akrawi, Sabah H. (Journal of Spectroscopy, 2019)
FDA has recently approved a new fixed-dose combination of amlodipine besylate (AMD) and celecoxib (COX) for the treatment of hypertension and osteoarthritis. No analytical method has been reported for analysis of these two analytes so far. Hence, to monitor the quality and quantity in the formulation of AMD and COX a simple, accurate, precise, economical, and eco-friendly spectroscopic analytical method has been established. The first method involves the determination of AMD and COX by the first derivative UV spectroscopic method with scaling factor 10. However, the second method was based on the direct measurement of UV absorbance of AMD at 364.3 nm and ratio first derivative UV spectroscopic method for COX. Both methods showed good linearity in the range of 5 to 40 μg/ml for COX, whereas AMD showed linearity in the range of 0.5 to 10 μg/ml in first derivative method with scaling factor 10 and 1 to 10 μg/ml in the second method with good correlation coefficient (R2 > 0.998). Both the methods were validated for LOD, LOQ, accuracy, precision, recovery studies, and stability as per the ICH guidelines, and the validated results were well within the acceptable range. Both the methods were successfully utilized for the determination of AMD and COX in the presence of each other in the formulation, and statistically compared between the proposed methods. Therefore, the proposed procedures can be utilized for regular quality control studies.